2020
DOI: 10.2166/wh.2020.162
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: urgent actions, critical reflections and future relevance of ‘WaSH’: lessons for the current and future pandemics

Abstract: The COVID-19 pandemic placed hygiene at the centre of disease prevention. Yet, access to the levels of water supply that support good hand hygiene and institutional cleaning, our understanding of hygiene behaviours, and access to soap are deficient in low-, middle- and high-income countries. This paper reviews the role of water, sanitation and hygiene (WaSH) in disease emergence, previous outbreaks, combatting COVID-19 and in preparing for future pandemics. We consider settings where these factors are particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 79 publications
1
81
0
3
Order By: Relevance
“…First, adequate handwashing requires sufficient water availability from easily accessible and reliable sources, with household piped water being the highest level of access. 34 Second, physical isolation at home for individuals suspected to have COVID-19 as well as the general population during periods of strict lockdown have been promoted as measures to reduce transmission.…”
Section: Discussionmentioning
confidence: 99%
“…First, adequate handwashing requires sufficient water availability from easily accessible and reliable sources, with household piped water being the highest level of access. 34 Second, physical isolation at home for individuals suspected to have COVID-19 as well as the general population during periods of strict lockdown have been promoted as measures to reduce transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, these measures are only feasible if there is adequate water, hygiene, and latrine facilities in a household; otherwise household members would need to access public locations to retrieve water, bathe, and defecate. 34 We found in our study that good WASH infrastructure enabled compliance with preventive measures like handwashing or staying home, as participants were able to use their latrine and wash their hands at home. A separate study in Tamil Nadu, India found that respondents of the same age, gender, and education who had access to a private toilet were more likely to report they increased the frequency of handwashing since the lockdown, 27 further suggesting that infrastructure played a role in COVID-19 handwashing practices.…”
Section: Discussionmentioning
confidence: 60%
“…Access to adequate WASH infrastructure can play a role in an individual's ability to comply with recommended COVID-19 preventative measures in two ways. First, adequate handwashing requires sufficient water availability from easily accessible and reliable sources, with household piped water being the highest level of access 34. Second, physical isolation at home for individuals suspected to have COVID-19 as well as the general population during periods of strict lockdown have been promoted as measures to reduce transmission.…”
mentioning
confidence: 99%
“…A rapid response was called for, and actors across the globe worked quickly to develop sets of preventative measures to contain the disease. One mode of transmission identified early on in the crisis was via surfaces and objects (fomites) (Howard et al 2020). To combat this, hand hygiene was put forward as a key preventative measure and heralded as 'the first line of defence against the disease' (World Bank 2020).…”
Section: Introductionmentioning
confidence: 99%